Age-specific differences in prognostic significance of rhythm conversion from initial non-shockable to shockable rhythm and subsequent shock delivery in out-of-hospital cardiac arrest. (November 2016) - Funada, Akira; Goto, Yoshikazu; Tada, Hayato; Teramoto, Ryota; Shimojima, Masaya; Hayashi, Kenshi; Yamagishi, Masakazu
Abstract: Background: Early rhythm conversion from an initial non-shockable to a shockable rhythm and subsequent shock delivery in patients with out-of-hospital cardiac arrest (OHCA) has been associated with favourable neurological outcome (Cerebral Performance Category score 1 or 2; CPC 1–2). We hypothesized that the prognostic significance of rhythm conversion and subsequent shock delivery differs by age and time from initiation of cardiopulmonary resuscitation (CPR) by emergency medical service (EMS) providers to first defibrillation (shock delivery time). Methods: We analysed 430, 443 OHCA patients with an initial non-shockable rhythm using a prospective Japanese Utstein-style database from 2011 to 2014. The primary endpoint was 1-month CPC 1–2. Results: Multivariate logistic regression revealed that rhythm conversion and subsequent shock delivery is positively associated with 1-month CPC 1–2: the adjusted odds ratio was 6.09 (95% confidence interval: 3.65–9.75) for shock delivery time <10 min and 3.34 (2.58–4.27) for 10–19 min in patients aged 18–64 years, and 3.16 (1.45–6.09) for <10 min and 2.17 (1.51–3.03) for 10–19 min in patients aged 65–74 years. However, it is negatively associated with 1-month CPC 1–2 for shock delivery time of 20–59 min in patients aged 75–84 years (0.55; 0.27–0.98) and ≥85 years (0.17; 0.03–0.53). Conclusions: Early rhythm conversion from an initial non-shockable to a shockable rhythm and subsequent shock delivery is associated with increased odds of 1-month CPC 1–2 in OHCA patients aged 18–74 years but not in those aged ≥75 years.